Patient’s Compliance with Oral Antibiotics Treatments at Community Health Centers in Surabaya: A 20-KAO Questionnaire Development - Ilil Maidatuz Zulfa; Widya Handayani (Borneo Journal of Pharmacy, 2020)
The irrational and incompliance use of antibiotics has been correlated to bacterial resistance. Several methods evaluated patients' compliance with oral antibiotics have been conducted. However, a standard questionnaire for evaluating oral antibiotics compliance in Indonesian has not been developed yet. This study was conducted to record the content validity of the developed questionnaire called 20-KAO to assess compliance with oral antibiotics. The validity content test was conducted through six experts review using the Item Content Validity Index (I-CVI) and Scale-Content Validity Index (S-CVI). The experts were also requested to provide recommendations for each item, whether revisions or deletion. After the review process, the number of questions remains unchanged. A total of 19 out of 20 items had an I-CVI of 1.00, and S-CVI was calculated at 0.98. Therefore, 20 items of the 20-KAO questionnaire have excellent content validity. However, future construct validity and reliability test to analyze the responses of targeted respondents and the questionnaire's consistency are needed.